Improving Health Outcomes and Health Care in India - Joumard, Isabelle (OECD Economics Department Working Papers, 2015)
With India's low life expectancy largely reflecting deaths from preventable diseases, the most significant gains in health would come from population-wide preventive measures. Access to public health care services varies substantially, resulting in many people turning to private-sector providers who mainly serve those who can pay. While government has scaled up public health services, more health professionals and public health care spending will be needed to ensure broad and adequate health-care coverage. Priority should be given to high impact primary health care services. For more resources to translate into better services, the management of public health care services needs to improve. The private sector can be drawn upon more extensively, but should also be obliged to meet basic quality standards